Embates discursivo-ideológicos em produções textuais escolares: alunos versus discursos institucionais - Costa, Valmir Nunes (2014)
This thesis focuses on the clash between ideological discourse among students of basic education and the discourses of the institution. Aims to describe linguistic processes desecration of institutional discourse conveyed in school. The locus of this process are the textual productions of the students, which materializes this ideological struggle in favor of centrifuge centripetal forces responsible for monologizating discourses (BAKHTIN, 2008b). With the terms centrifugation and centripetal forces, we mean modalization inflexible institutional discourses or relativization / institutional dispersal directions by these students. The files found in both phase conjectures and after the reading and interpretation of the corpus (for he had experience of the author in the field of education), were of irony, parody, implicit sarcasm, approach the grotesque, humor, subversion, between the main, which, seen as a whole, call carnival. Such mechanisms play with the institutional discourses in order to strip them of classes and interests hiding of reality that are the counterpoint of totalitarian discourse aimed at maintaining the status quo. Through the categories of Discourse Analysis of French brands we aim to explain the language of the speeches of students who exhibit an attitude linguistic / discursive able to disperse senses, but also to arouse them before institutional discourses conveyed in school and tend controller senses. Beside theories of AD, we work with the perspective of Bakhtin studies regarding the notions of language, ideology and carnivalization.